Peran Orangtua Terhadap Hasil Belajar Kognitif Siswa Kelas III SDN Sumur Peteuy Baros Tahun Ajaran 2019/2020 - Roihatul Farida Maulidi; Sani Insani Muhamadi (Jurusan Pendidikan Guru Madrasah Ibtidaiyah Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2020)
Abstract. This research is motivated by the findings of problems obtained from parents' complaints about student learning outcomes at school, because it is difficult for parents to guide their children to study at home since the Covid 19 outbreak in Indonesia. In addition, it is difficult for children to be asked to learn by their parents and to do assignments from the teacher who are sent through social media. Apart from that lack of parental knowledge. The purpose of this study was to determine the role of parents on student cognitive learning outcomes, to determine student cognitive learning outcomes, the relationship between parental roles and cognitive learning outcomes of third grade students at SDN Sumur Peteuy Baros for the 2019/2020 academic year. The method used in this research is correlation. Types and sources of data used are quantitative data, while data sources used are primary and secondary data. Data collection techniques are using questionnaires and documentation. The conclusion in this study is that it shows that rcount is greater than rtable (0.633> 0.312) so that H1 is accepted, this means that there is a positive and significant relationship between the role of parents on the cognitive learning outcomes of third grade students of SDN Sumur Peteuy, Baros District. In the interpretation the relationship is included in the high category at the interval 0.60-0.799. Keywords: The Role Of Parents, Cognitive Learning outcomes